Impact of oat grain supplementation on growth performance, rumen microbiota, and fatty acid profiles in Hu sheep - Ren, Xiaoqi; Wang, Liwei; Yu, Chuanzong; An, Jianghong; Fu, Shaoyin; Sun, Hua; Zhao, Mengran; Te, Rigele; Bai, Xiaobo; Yuan, Jingda; Liu, Yongbin; He, Jiangfeng (Frontiers in Microbiology, 2025)
The intestinal microbiota plays a vital role in animal growth and development. In this study, we explored the impact of oat grain dietary supplementation on growth performance, intestinal microbiota, short-chain fatty acids (SCFAs), and fatty acids (FAs) in Hu sheep. Thirty-two Hu lambs were randomly assigned to a control group (RC) or an oat grain-supplemented group (RO). After 90 days on their respective diets, rumen digesta were collected from six randomly selected Hu lambs per group to assess microbial diversity, SCFAs, and FAs. The RO diet significantly enhanced growth in Hu sheep (p < 0.01) and increased α-diversity, as indicated by Chao1 and Shannon indices. Core phyla in both groups were Firmicutes and Bacteroidota, with predominant genera including Prevotella, Rikenellaceae_RC9_gut_group, and F082. Oat grain supplementation led to significant shifts in microbial composition, increasing the abundance of Acidobacteriota, Proteobacteria, Chloroflexi, Actinobacteriota, and Subgroup_2, while decreasing Bacteroidota and Oscillospiraceae (p < 0.05). The RO group also exhibited lower levels of isobutyric and citraconic acids but higher levels of azelaic acid (p < 0.05). These results indicate that oat grain supplementation enhances beneficial rumen microbes and optimizes FAs and SCFAs composition, thereby promoting weight gain in Hu sheep.